ORGANIZATION OF PREPARATION OF PARTICIPANTS OF OLYMPIAD FROM INFORMATICS BY FACILITIES OF INTERNETPORTAL OF E-OLIMP - S. S. Zhukovskiy (Kherson State University, 2010)
In the article the organizational section of Internetportal is described organizationally methodical providing of preparation of the controlled from distance olympiads from programming for the gifted young people of educational establishments of Ukraine. The method of preparation of students is developed to the olympiad from programming of Internetportal E-OLIMP facilities.